Evaluation of mechanical and free vibration properties of the pineapple leaf fibre reinforced polyester composites - Senthilkumar, Krishnasamy; Saba, Naheed; Chandrasekar, Muthukumar; Jawaid, Mohammad; Rajini, N.; Alothman, Othman Y.; Siengchine, Suchart (Elsevier, 2019)
Pineapple Leaf Fibre (PALF) Reinforced Polyester (PE) composites were fabricated by hand lay-up using randomly oriented PALF in PE matrix, compressed at 17 MPa by compression moulding. Effect of PALF loading in PE composites on mechanical, morphological, free vibrational and damping properties were investigated. Result analysis revealed that the tensile, compressive strength and flexural properties considerably increased with increasing PALF loading according to the rule of mixtures. Moreover, SEM images of tensile fracture samples shows relatively less fibre pull-out, fibre breakage and improved fibre/matrix adhesion due to effective stress transfer with the increased PALF loading in PE composites. Natural frequency improved while damping ratio decreased as a result of increasing the PALF loading in PALF/PE composites. Finally, a composite with 45 wt% PALF loading is found as suitable replacement for structural component in construction industries.